Penguatan Branding dan Pemasaran Digital bagi UMKM Kerupuk Rambak Sapi Sapariyah - Hikmah Fratiwi, Tria; Edwar; Arie Pratama, I Putu; Anggelina , Cherlin; Agung Bagus Pramana Putra Suada, Anak (Insan Kreasi Media, 2025)
This community service activity aims to enhance the sustainability and competitiveness of the Kerupuk Rambak Sapi Sapariyah business in the digital era through the Participatory Action Research (PAR) approach. The program consists of five main stages: resource identification (to know), problem identification (to understand), solution strategy planning (to plan), solution strategy implementation (to action), and evaluation (to reflection). The initial stages focus on identifying resources and core issues, such as unappealing branding, limited digital marketing capabilities, and production inefficiencies. Based on these findings, strategic solutions were designed, including creating a new logo and packaging, conducting digital marketing training, mentoring in social media management, developing marketing content, and providing essential production tools like stoves and oil-draining spinners to improve operational efficiency. These solutions were implemented in stages with active participation from the business owner to ensure effective collaboration. Evaluation was conducted based on performance indicators, such as improvements in product quality, operational efficiency, and market reach. The program's results demonstrate significant changes in the business's sustainability and competitiveness, highlighting the potential of PAR as an impactful and sustainable model for supporting small business development through community engagement.